THE RELATIONSHIP BETWEEN KNOWLEDGE, EDUCATION AND HUSBAND SUPPORT WITH ACETIC ACID VISUAL INSPECTION (IVA) EXAMINATION - Edi Wiranti, Listiani; Putu Lusita Nati Indriani; Fika Minata Wathan; Sendy Pratiwi R (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Cervical cancer occurs in the uterine cervic, an area in the female reproductive organs which is the entrance to the uterus and vagina. The causes of cervical cancer include enganging in sexual partners. This study aims to determine the relationship among knowledge, education, husband’s support, and the examination of Visual Inspection of Acetic Acid (IVA) in Burnai Mulya Public Health Center Working Area East Ogan Komering Ulu Regency. The study employed an analytical survey method with a cross-sectional approach. The population in this study was all women of childbearing age (WUS) Who Visited Burnai Mulya Public Health Center in March – July 2024 as many as 158 respondents. Sample was taken using accidental sampling technique with a total sample size of 53brespondents. The analysis was univariate and bivariate analysis wiyh chi square statistical tests. The results of univariate analysis showed that 53 respondents, mothers who performed IVA examination were 25 respondents (47,2%) and mothers who did not perform IVA Examination were 28 people (52,8%). The Bivariate results using the chi square test found that there was a relationship between knowledge (p value =0,004) and mothers education (p value = 0,000), husband’s support (p value = 0,004) and acetic acid injection (IVA) Examination Burnai Mulya Public Health Center. This study is expected to contribute as additional references and literature for students, provide information to the public about acetic acid inspection (IVA), and improve the quality of services to prevent cervical cancer.